A novel dual-LED based long-path DOAS instrument for the measurement of aromatic hydrocarbons. (December 2016) - Stutz, Jochen; Hurlock, Stephen C.; Colosimo, Santo F.; Tsai, Catalina; Cheung, Ross; Festa, James; Pikelnaya, Olga; Alvarez, Sergio; Flynn, James H.; Erickson, Matthew H.; Olaguer, Eduardo P.
Abstract: Aromatic hydrocarbons are well known air toxics which are regulated by the US EPA and other air quality agencies. Accurate, long-term monitoring of these compounds at low part-per-billion levels, as well as identifying emission point sources is therefore crucial to protect human health in neighborhoods near large emission sources. Here we present a new long-path differential optical absorption spectroscopy (LP-DOAS) instrument specifically designed to monitor aromatic hydrocarbons. The system is based on a novel dual - light emitting diode (LED) light source, which eliminates the requirement to suppress spectrometer stray light. This light source, together with a high stability fiber-based sending/receiving telescope, allows the measurement of aromatic hydrocarbons on once-folded absorptions paths of 200–1200 m length. The new instrument shows very good agreement with simultaneous in-situ measurements if inhomogeneities of the trace gas spatial distributions are considered. The new instrument performed well during a three-month field test as an automated fence-line monitor at a refinery, successfully distinguishing upwind background levels of ∼1 ppb from emissions reflected in elevated mixing ratios of 3–4 ppb. A two-dimensional measurement network based on two identical LP-DOAS instruments operating on seven crossed light paths was operated successfully in Houston, TX. Qualitative and quantitative analysis of two events with toluene and xylene plumes demonstrate how this setup can be used to derive the spatial distribution of aromatic hydrocarbons, and identify point sources. Highlights: A new instrument for fence-line monitoring of aromatic hydrocarbons was developed. A novel dual-LED light source improves LP-DOAS observations of aromatics. Accurate LP-DOAS observations of benzene, toluene and xylenes were demonstrated. Two-dimensional concentrations fields were determined using Tomographic LP-DOAS.